A systematic review of medical and non-medical practitioners' views of the impact of ehealth on shared care. Issue 1 (11th October 2013) - MacLure, Katie; Stewart, Derek; Strath, Alison
Abstract : Purpose: To explore medical and non-medical practitioners' views of the impact of ehealth on shared care. Method: A systematic review was conducted using a meta-narrative approach with publication search dates limited from 1 January 2005 to 28 February 2011 and English language only. Search results from the databases (ASLIB, EBSCO Host, Cochrane Library, Informa Healthcare, PsycNet, Sciverse Scopus, Zetoc) were independently reviewed and data extracted by two of the authors. The review included peer reviewed papers about medical and non-medical practitioners who provide ehealth supported shared care. Articles which focused solely on searching the internet or exchange of emails were excluded. Results: Screening reduced the initial 327 papers identified to 12 which included three reviews, four qualitative, two mixed methods and three quantitative studies. Included studies collected data using combinations of questionnaires, case study, group/individual interviews, observation and extraction of data from records. Data were analysed using thematic, interpretive, analytic induction/constant comparative and statistical analysis methods. Practice settings were primary care, secondary care or both. The focus was on electronic records (7), telemedicine (2) or general ehealth implementation (3) predominantly from the perspective of doctors, nurses, IT developers, policy makers and managers plus one hospital pharmacist. The studies showed acceptance of ehealth technologies to support increasing levels of shared care but with cost effectiveness, level of resourcing and training questioned by respondents. Emerging themes across all study types were organisational, social and technical: resource and time implications, culture of the workplace and change management requirements; impact on patient consultation, extra workload, need for training suited to varying levels of IT literacy, usability, patient privacy and the practitioner's role; systems incompatibility, technological inadequacies, need for shared definition and terminology. Conclusions: Findings indicate acceptance of ehealth to support shared care but question anticipated efficiencies. Organisational, social and technical issues identified were similar to non-healthcare IT implementations and adoption of innovation theory. Evidence of medical and non-medical practitioners' views of the impact of ehealth on shared care remains limited with further areas for pharmacy ehealth research identified.